Factors of Coastal Tourism Management with DPSIR Analysis (Case Study: Tanjung Lesung Special Economic Zone, Pandeglang Regency, Banten Province) - Lilis Sri Mulyawati; Luky Adrianto; Kadarwan Soewandi; Handoko Adi Susanto (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
Tourism in general is often seen as an opportunity to promote economic and social development, as well as coastal tourism. Coastal tourism activities are also a driving force that can affect ecosystem structures and processes and reduce existing resources on the coast. The research aims to manage tourism coastal areas, both mainland and waters, therefore integrated zone development and sustainable between land and water can be realized. DPSIR analysis (Drivers, Pressure, State, Impact, Response) is a descriptive study with primary and secondary data obtained from respondents (tourist, community, expert) and literature review. The analysis was carried out with qualitative analysis and to test the results of the literature review and the results of field observations, an expert survey was carried out so that the factors in the management of coastal tourism in an area designated as a tourism zone were obtained. The dominant factors resulting from the DPSIR analysis can be concluded as influencing factors in the management of coastal tourism so that they will provide solutions for the realization of an ecologically, socially, and economically sustainable tourism area plan. Suggestions to managers, both private and government, to keep the environment in order to create a sustainable tourist area.